Trend of Critical Discourses Analysis Researches in Linguistics Journals of Sinta 1 to 4: from CDA model to Research Design - Mutakhirani Mustafa; Nirwana; Nelly Husni Laely; Emi Anggreani Masjur; Eka Pitra (Universitas Islam Negeri Palopo, 2025)
The 21st century linguistic study aims to achieve various goals, and one of them is the empowerment of Critical Discourse Analysis as constructivist approach on linguistic study. This study utilized content analysis as a research method, specifically employing a document scanning approach. The articles selected for analysis were retrieved from the websites of Sinta1 to 4 in Indonesia between 2016 and 2022. To compile a list of journals indexed in the Sinta, the researchers accessed the Sinta and conducted a keyword search using